2012
DOI: 10.5120/8846-3040
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition based on a Hybrid Meta-heuristic Feature Selection Algorithm

Abstract: For the past few years, a number of new face recognition techniques have been proposed. Always it is a big unanswered question among face recognition researchers about which method or technique will have better performance. In this study an approach to recognize known faces based on Eigen vectors and a hybrid Meta-heuristic feature selection algorithm is proposed. The eigenvectors which are covariance matrix of the face images together describes the difference between face images. Face recognition problem is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The service deployment has been peak due to development edge computing in research field to reduce the delay, storage process. The [15] introduced the algorithm for optimizing the interactions between edge components in big data management and cloud. By combining the edge computing with cloud computing, became new technology for networks and communication.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The service deployment has been peak due to development edge computing in research field to reduce the delay, storage process. The [15] introduced the algorithm for optimizing the interactions between edge components in big data management and cloud. By combining the edge computing with cloud computing, became new technology for networks and communication.…”
Section: Literature Surveymentioning
confidence: 99%
“…Several cloud computing servers communicate with the edge computing components in transferring the data. The main problem in previous edge-cloud hybrid server is communication bandwidth in the network between the cloud computing servers and edge computing servers increases the complexity of the system [15]. To overcome this in our architecture we have only one cloud servers and few edge devices.…”
Section: Fig 2: Service Dependency Modelmentioning
confidence: 99%
“…This research has developed prediction techniques to enhance the day-to-day forecast of electricity prices through multi-stage optimization of Least Square Support Vector Machine (LSSVM) and Bacterial Foraging Optimization Algorithm (BFOA). BFOA has been applied in a number of areas such as face identification [15], [16], biometric verification [17], multimodal functions [18], flexible manufacturing systems (FMS) [19], control and power systems [28], [34]. To date, the authors have found no studies that incorporate LSSVM and BFOA in electricity pricing prediction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this study introduces a new technique in electricity price forecast by developing hour-ahead electricity price forecasting model with Least Square Support Vector Machine (LSSVM) and Bacterial Foraging Optimization Algorithm (BFOA). BFOA has a fast convergence [12] and has been explored in many fields such as face recognition [13], [14], biometric authentication [15], multimodal function [16], [17], and flexible manufacturing systems (FMS) [18]. Furthermore, researchers in control and power system developed BFOA models for Static Synchronous Series Compensator (SSSC) Damping Controller Design [19], robotic manipulator workspace optimization [20], three phase induction motor and electricity load forecasting [28], [34].…”
mentioning
confidence: 99%